Validation of a NaI(Tl) and LaBr3(Ce) detector's models via measurements and Monte Carlo simulations. Issue 4 (October 2018) - Mouhti, I.; Elanique, A.; Messous, M.Y.; Belhorma, B.; Benahmed, A.
Abstract: This work relates to the study and characterization of the response function of two scintillation detectors with similar size: 2″×2″ NaI(Tl) and 2″×2″ LaBr3 (Ce). The photon detection efficiency and energy resolution curve were measured for the NaI(Tl) detector in the gamma energy range from 60 keV to 1408 keV. A precise mathematical model of the two scintillators was developed using the Monte Carlo simulation code MCNP. Comparison of the efficiency data with MCNP simulations showed good agreement enabling the validation of the computational models for both NaI(Tl) and LaBr3 (Ce) detectors.